Inhaled corticosteroids in COPD: friend or foe?. Issue 6 (13th December 2018) - Agusti, Alvar; Fabbri, Leonardo M.; Singh, Dave; Vestbo, Jørgen; Celli, Bartolome; Franssen, Frits M.E.; Rabe, Klaus F.; Papi, Alberto
The efficacy, safety and positioning of inhaled corticosteroids (ICS) in the treatment of patients with chronic obstructive pulmonary disease (COPD) is much debated, since it can result in clear clinical benefits in some patients ("friend") but can be ineffective or even associated with undesired side effects, e.g. pneumonia, in others ("foe"). After critically reviewing the evidence for and against ICS treatment in patients with COPD, we propose that: 1) ICS should not be used as a single, stand-alone therapy in COPD; 2) patients most likely to benefit from the addition of ICS to long-acting bronchodilators include those with history of multiple or severe exacerbations despite appropriate maintenance bronchodilator use, particularly if blood eosinophils are >300 cells·µL −1, and those with a history of and/or concomitant asthma; and 3) the risk of pneumonia in COPD patients using ICS is higher in those with older age, lower body mass index (BMI), greater overall fragility, receiving higher ICS doses and those with blood eosinophils <100 cells·µL −1 . All these factors must be carefully considered and balanced in any individual COPD patient before adding ICS to her/his maintenance bronchodilator treatment. Further research is needed to clarify some of these issues and firmly establish these recommendations. The use of inhaled corticosteroids in patients with COPD must be personalised http://ow.ly/ZyFI30lDfUR